PEDAGOGICAL ARTISTISM AS A PROFESSIONAL AND PERSONAL CHARACTERISTICS OF A FUTURE TEACHER-MUSICIAN - Okhunjon Ilkhomjonugli Kimsanov (Web of Journals Publishing, 2023)
The article discusses pedagogical artistism as a professional and personal characteristic of a future teacher-musician.
Keywords: music, pedagogy, methodology, piano, pedagogical university.